Сomparative analysis of economic efficiency application of milling excavator working equipment for pipeline undermining - I. S. Kuznetsov (Вестник СибАДИ, 2021)
Introduction. The use of pipeline transport for the movement of hydrocarbons and petroleum products is the main strategic system of Russia with a huge volume of cargo turnover. The share of pipeline transport in the freight turnover of the Russian transport system is over 48 %. Maintenance of the pipeline system is impossible without the use of mechanization and special equipment. So, to restore its working condition, various options for sets of machines are used.Implementation of the methodology. As a result of the research carried out, a set of machines was selected for performing the technological operations of the overhaul of a section of the steel main pipeline. The main technical and economic indicators are calculated, taking into account the efficiency and expediency of using a set of machines.Results. The economic efficiency of a set of machines, including a hydraulic excavator with a developed milling working equipment, the novelty of which is confirmed by patents for a useful model of the Russian Federation, has been determined.Discussion and conclusions. The directions of further research are the calculation and substantiation of the necessary operating parameters for the introduction into operation of the milling working equipment of a hydraulic excavator.